Lidocaine Treatment in Refractory Status Epilepticus Resulting from Febrile Infection-Related Epilepsy Syndrome: A Case Report and Follow-Up - Capizzi, Giorgio; Vittorini, Roberta; Torta, Francesca; Davico, Chiara; Rainò, Elena; Conio, Alessandra; Longobardo, Annalisa; Briatore, Eleonora; Podestà, Barbara; Calzolari, Stefano (Neuropediatrics, 2015)
We report the management of refractory status epilepticus (SE) by using continuous intravenous infusions of lidocaine in a previously healthy 15-year-old girl with a “catastrophic encephalopathy” in whom a diagnosis of febrile infection-related epilepsy syndrome was supposed. One week after a banal pharyngitis and fever, the patient presented confusion and intractable clusters of seizures. Although she underwent multiple examinations investigating all possible etiologies (intracranial infection, autoimmune disease, or toxic and metabolic illness), all results were negative except a feeble positivity to Mycoplasma pneumoniae serum antibodies. SE was initially treated with benzodiazepine followed by administration of barbiturates and subsequent induction of coma because of refractory SE; different antiepileptic drugs (AEDs) were given at different times in a period of 6 weeks but clinical and electroencephalographic improvements were achieved only after continuous infusion of lidocaine. When she recovered from SE, the patient developed severe psychomotor and cognitive impairment associated with cerebral atrophy. Treatment with lidocaine or other alternative drugs in cases of prolonged SE should be taken into account as soon as it becomes clear that the clinical condition is refractory to common AEDs included in available guidelines for SE treatment, to improve the bad outcome of this severe condition, at least limiting the negative effects of prolonged high metabolic demand due to continuous epileptiform activity and/or the possible negative effects of prolonged burst-suppression coma.
Keywords: FIRES; children; epilepsy; lidocaine; status epilepticus